EMPOWERING VILLAGE GOVERNMENTS THROUGH PARTICIPATORY TRAINING MANAGEMENT CYCLE: IMPLEMENTATION OF THE SIK ELHAN HEALTH INFORMATION SYSTEM IN TOMOHON CITY - Oksfriani Jufri Sumampouw; Jeini Ester Nelwan (International Journal of Multidisciplinary Reseach, 2026)
Health data management at the village level in Tomohon City faces significant challenges, including limited human resource capacity, non-integrated systems, and manual data collection that hinders the planning of priority health programs. This Community Service Program (PKM) aims to address these issues by establishing an information system and building the capacity of village officials, with the primary outcome being the creation of a sustainable Village Health Information System (SIK ELHAN). Methods: The study employed a participatory Training Management Cycle approach, consisting of four stages: (1) Training Needs Assessment to identify partner requirements; (2) Training Design to develop training programs and system architecture; (3) Training Delivery involving hands-on training, tutorials, and direct mentoring; and (4) Training Evaluation using Key Performance Indicators (KPIs) to measure effectiveness and impact. This methodology actively engaged partners throughout all stages. Results: The program successfully developed and implemented SIK ELHAN, a web-based system enabling structured and real-time recording and reporting of community health data. Thirty village officials and healthcare workers were trained, with 85% of participants demonstrating independent system operation capability. Evaluation results showed a 70% increase in participant understanding based on pre-test and post-test comparisons. The Village Government demonstrated strong commitment to sustainability by appointing dedicated administrators for SIK ELHAN management, supported by a 90% partner satisfaction rate. The participatory Training Management Cycle approach proved effective not only in providing the technical solution of SIK ELHAN but also in empowering partners through capacity building. This program successfully established a robust foundation for digital transformation of health data management at the village level, which is expected to support more effective data-driven health program planning and monitoring in Tomohon City.